(untitled) (LEARNing Landscapes, 2012)
This paper draws on a long-term multi-site narrative inquiry into the curriculummaking experiences of children, families, and teachers. We draw upon our earlier understandings of two worlds of curriculum making, the familial and the school, to inquire into tensions shaped for one family, in a place of school, as they experienced the meeting of their familial curriculum-making world with the school curriculummaking world. Familial curriculum making is curriculum making in which children are engaged as they interact with family and community members. We wonder how we might move forward as we create situations with children in both curriculum-making worlds, situations in which they can find ways of making sense of the two constructions of themselves in these two worlds.